Konsep Perlindungan Korban dalam Sistem Peradilan Pidana Nasional dan Sistem Hukum Pidana Islam - Ariyanti, Vivi (Fakultas Syariah IAIN Purwokerto, 2019)
The current position of victims in the criminal justice system has not been placed fairly, because victims in the judiciary are only represented by public prosecutors who base their charges on statutory rules and facts obtained from witnesses. This paper reviews and compares the Indonesian national criminal justice system and Islamic criminal law system in terms of protecting the rights of victims of criminal acts during and after undergoing the trial process. The study of victims in the Western criminal law system adopted by Indonesia has been so extensive and profound, that it raises its own science called victimology, which is parallel to the science of criminology. Meanwhile Islamic criminal law (al-Fiqh al-Jinayah) still refers to fiqh books written by medieval jurists, so that the study of Islamic criminal law is stagnant and without significant progress. However, both national criminal law and Islamic criminal law, in principle, emphasize that the protection of victims must be balanced between the interests of the victims themselves, the perpetrators of crime, society, the state, and the public interest.